Trends of solar radiation effects on the temperature of vertical surfaces of a modern terrace house. Issue 6 (25th April 2021) - Ismail, Mohd Rodzi; Rasli, Nur Baitul Izati; Ramli, Nor Azam
Abstract: This is a study done to investigate the effects of solar radiation on the wall surface temperature of a modern terrace house. It involves the analysis of the thermal fluctuations of common building materials used for walls or vertical surface areas such as the bricks, glass of the window, and metal doors. A thermal imager and data logging system was used in collecting the data for the Southeast and Northwest façades of the house. The imager gave resourceful data on the thermal heat trend of the walls and their surface temperature. The results show that a lighter wall surface color reduces the temperature of the surface. Furthermore, the bricks, which have a higher density hence a higher absorptivity due to their high capacity for storage of heat, decrease the flow of heat. However, the use of tinted glass on windows increases the surface temperature of the glass area of the wall surface. The metal also shows a high similarity with glass in terms of its thermal performance. In conclusion, the types of material used on wall surfaces have a significant impact on the wall temperature.